Fixed-bed adsorption of Eriochrome Black T and Reactive Blue 19 dyes onto carbonized Coix lacryma-jobi (Adlai) shells - Paculan, Anthea Kristine Y.; De Luna, Mark Daniel G. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Adsorbent derived from Coix lacryma-jobi (adlai) shells, carbonized adlai (CA), was used to remove anionic dyes, Eriochrome Black T (EBT) and Reactive Blue 19 (RB 19), in fixed-bed experiments. The effect of influent dye concentration, volumetric flowrate, and dye type on the adsorption process were investigated. The Yoon-Nelson, Thomas, and Bohart-Adams theoretical models were employed to predict the performance of fixed-bed adsorption operations. Overall, both the Thomas and Yoon-Nelson models (r2 = 0.937-0.989) best describe the adsorption of EBT and RB19 onto CA at varying influent dye concentration and volumetric flowrate in a fixed-bed. The Bohart-Adams model (r2= 0.950-0.999) best describes the adsorption of EBT and RB19 onto CA adsorbent for the initial part of the adsorption process. The rate constants, kT and kBA decreased, and kYN increased, with increased concentration, whereas all rate constants increased with increased flow rate. The calculated parameters obtained through the models were in good agreement with the experimental result. It was observed that the time at 50% breakthrough decreased with increased influent concentration and flow rate. Adsorption capacities, q and N0, increased with increased concentration, but decreased with increased flow rate. It was also observed that CA has a higher affinity towards the adsorption of RB 19 than EBT.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Adsorption; Sewage -- Purification -- Color removal; Adlai shells